The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10661-007-9606-5
|View full text |Cite
|
Sign up to set email alerts
|

Fish scales as bio-indicator of water quality of River Ganga

Abstract: Various studies have been conducted in the past on the fresh waters related to the various aspects of limnology, physico-chemistry, primary productivity, plankton etc. in relation to environmental conditions and ecology, flora and fauna of River Ganga. In the present investigation some recent approach have been made to study the various parts of fishes like gill structures, scales for age determination, length and weight of fish for growth assessments etc. The SEM study of scales in relation to pollution and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 1 publication
0
29
1
1
Order By: Relevance
“…BOD has been used to detect the amount of organic materials in water which supports the growth of microorganism (Goel, 2006). In the present study, the average value found was 4.6mg/l is higher than the value obtained by the in Yamuna River (Khaiwal, et al, 2003) and in Ganga River (Khanna, et al,2007) correspondingly.…”
Section: Biological Oxygen Demand (Bod):-contrasting
confidence: 76%
“…BOD has been used to detect the amount of organic materials in water which supports the growth of microorganism (Goel, 2006). In the present study, the average value found was 4.6mg/l is higher than the value obtained by the in Yamuna River (Khaiwal, et al, 2003) and in Ganga River (Khanna, et al,2007) correspondingly.…”
Section: Biological Oxygen Demand (Bod):-contrasting
confidence: 76%
“…The average value of 11 years was found as 1.84 ± 0.32 mg/l. Khaiwal et al (2003) and Khanna et al (2007) noted the similar thing in river Yamuna and in river Ganga correspondingly. The minimum value as well as maximum value of chemical oxygen demand was observed to be 8.69 ± 0.56 and 12.00 ± 0.68 mg/l, respectively.…”
Section: A-physiochemical Parametersmentioning
confidence: 74%
“…The average value of 11 years was found as 81.74 ± 12.24 mg/l. Khanna et al (2007) found average value of total hardness 12.71 mg/l while working on river Ganges. The nitrate ranged from 0.02 to 0.07 mg/l, while Phosphate fluctuated from 0.05 to 0.08 mg/l.…”
Section: A-physiochemical Parametersmentioning
confidence: 94%
See 1 more Smart Citation
“…Fish are always susceptible to a wide range of pathogens that cause several types of diseases in skin, liver, kidney, and other organs Nandi et al, 2016). In a study Khanna, Sarkar, Gautam, and Bhutiani (2007) have reported the relation between water pollution and scale morphology, that might be helpful in monitoring environmental pollution. In a similarly study, Dua and Gupta (2005) also have observed the toxic effects of mercury on fish scale and correlated the effect with the water pollution.…”
Section: Effect On Scale Structure Revealed Through Light Microscopementioning
confidence: 99%